Mycobacterium leprae-Specific Antibodies in Multibacillary Leprosy Patients Decrease During and After Treatment With Either the Regular 12 Doses Multidrug Therapy (MDT) or the Uniform 6 Doses MDT - Hungria, Emerith M.; Bührer-Sékula, Samira; Oliveira, Regiane M.; Aderaldo, Lúcio C.; Pontes, Maria Araci A.; Cruz, Rossilene; Gonçalves, Heitor S. de; Penna, Maria L. F.; Penna, Gerson O.; Stefani, Mariane M. A. (Frontiers in Immunology, 2018)
Leprosy serology reflects the bacillary load of patients and multidrug therapy (MDT) reduces Mycobacterium leprae specific antibody titers of multibacillary patients/MB. The Clinical Trial for Uniform Multidrug Therapy Regimen for Leprosy Patients in Brazil, (U-MDT/CT-BR) compared outcomes of regular 12 doses MDT/R-MDT and the uniform six doses MDT/U-MDT for MB leprosy, both of regimens including rifampicin, clofazimine and dapsone. This study investigated the impact of R-MDT and U-MDT and the kinetic of antibody responses to M. leprae-specific antigens in MB patients from the U-MDT/CT-BR. We tested 3,400 serum samples from 263 MB patients (R-MDT:121; U-MDT:142) recruited at two Brazilian reference centers (Dona Libânia, Fortaleza, Ceará; Alfredo da Matta Foundation, Manaus, Amazonas). ELISAs with three M. leprae antigens (NT-P-BSA: trisaccharide-phenyl of PGL-I; LID-1: di-fusion recombinant protein and ND-O-LID: fusion complex of disaccharide-octyl of PGL-I and LID-1) were performed using around 13 samples per patient. Samples were collected at baseline/M0, during MDT (R-MDT:M1-M12 months, U-MDT:M1-M6 months) and after MDT discontinuation (first, second year). Statistical significance was assessed by the Mann-Whitney U test for comparison between groups (p values <0.05). In R-MDT and U-MDT groups, males predominated, median age was 41 and 40.5 years, most patients were borderline-lepromatous/BL and lepromatous/LL leprosy (R-MDT:88%, U-MDT: 90%).The bacilloscopic index/BI at diagnosis was similar (medians: 3.6 in the R-MDT and 3.8 in the U-MDT group). In R-MDT and U-MDT groups, a significant decline in anti PGL-I positivity was observed from M0-M5 (p=0.035, p=0.04 respectively), from M6-M12 and at the first and second year post treatment (p<0.05). Anti-LID-1 antibodies declined from M0-M6 (p=0.024), M7-M12 in the R-MDT; from M0-M4 (p=0.003), M5-M12 in the U-MDT and post treatment in both groups (p>0.0001). Anti ND-O-LID antibodies decreased during and after treatment in both groups, similarly to anti PGL-I antibodies. Intraindividual serology results in R-MDT and U-MDT patients showed that the difference in serology decay to all three antigens was dependent upon time only. Our serology findings in MB leprosy show that regardless of the duration of the U-MDT and R-MDT, both of them reduce M. leprae-specific antibodies during and after treatment. In leprosy, antibody levels are considered a surrogate marker